A Partially Etched Structure of Light‐Addressable Potentiometric Sensor for High‐Spatial‐Resolution and High‐Speed Chemical Imaging. Issue 15 (24th March 2018) - Truong, Hoang Anh; Werner, Carl Frederik; Miyamoto, Ko‐ichiro; Yoshinobu, Tatsuo
Abstract : In this study, a partially etched structure of a light‐addressable potentiometric sensor (LAPS) is fabricated for high‐spatial‐resolution and high‐speed imaging of chemical species. An anisotropic etching process based on tetramethylammonium hydroxide (TMAH) is optimized to fabricate the structure, which strikes a balance between the imaging performance and the mechanical strength of the sensor plate. The etched region of the sensor plate with a thickness of 47 µm yields a 12‐fold enhancement of the photocurrent signal at a high frequency of 120 kHz and a 10‐fold frequency bandwidth in comparison with the frame region with a thickness of 150 µm due to the reduced traveling distance of charge carriers inside the semiconductor. This result represents a new approach for high signal‐to‐noise ratio, high‐spatial‐resolution, and high‐speed measurement. Abstract : An anisotropic etching process based on tetramethylammonium hydroxide (TMAH) is optimized to fabricate a partially etched structure of a LAPS sensor plate. This structure results in an improved imaging performance inside the etched region while maintaining the mechanical strength of the sensor plate.